Relationships of Using Social Media Online to Learning English at the English Program, STBA YAPARI-ABA Bandung - Vindy Melliany Puspa (Humaniora, 2018)
The purpose of this research was to get the information on the frequency of using social media, identify the types of social media features, and prove the relationship between the frequency of using social media in English learning. This research used quantitative approach. Data were collected through a questionnaire distributed on a propotional random sampling that were analyzed using descriptive statistics. The respondents were 100 students, taken from several classes of regular students in Bachelor Degree in Semester VI and VIII of English program in STBA Yapari-ABA Bandung. The results show that most respondents have more than three social media accounts (71%). Youtube is the site that the most influential respondents (53%). The most useful social media feature is ‘sharing’ (54%) while the most frequently used part of the sentence is 'phrase' (42%). The most beneficial language ability is vocabulary (31%). There are other descriptive data describing the frequency of various English related activities in the use of respondents' social media. In addition, it is evident that there is a positive correlation, although its correlation value is very weak (Spearman rho: 0,098) between the frequency of social media usage with the acquisition of English indicated by the GPA.